Implementation Of Law Enforcement Of Hand-Catching Operations (OTT) IN LAW Number 19 Of 2019 - Krisdayanti, Aprilia; Putri, Edelweiss Premaulidiani (Universitas Islam kadiri, 2025)
Corruption in Indonesia is increasingly becoming a topic of discussion along with the debate over the revision of the KPK Law and the election of a new chairman of the